PENANAMAN NILAI TOLERANSI UNTUK MENINGKATKAN PERSATUAN ANTAR PESERTA DIDIK DI PESANTREN AR RISALAH - Umi Sa'adah; Mahliga Fitriansyah (JISPE Journal of Islamic Primary Education, 2026)
Indonesia, as a multicultural nation, faces significant challenges in maintaining national unity amidst its diversity. Islamic boarding schools (pesantren), as the oldest and most deeply-rooted Islamic educational institutions in Indonesia, occupy a strategic position in instilling tolerance values in the younger generation. This study aims to examine the process of inculcating tolerance values at Pesantren Ar Risalah (As-Salam Riyadhul Jannah), identify the strategies applied, and analyze their impact on promoting unity among students (santri). The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, documentation, and Focus Group Discussions (FGD) involving the pesantren leadership, teachers, male and female students, and alumni. The findings reveal that the cultivation of tolerance values is implemented through seven principal strategies: (1) exemplary conduct (uswah hasanah), (2) contextualized classical text study, (3) discussion and bahtsul masail methods, (4) heterogeneous dormitory life, (5) cross-cultural social and extracurricular activities, (6) the cultivation of religious moderation (wasathiyah), and (7) habituation and educative sanctions. These strategies have proven effective in enhancing unity, reducing conflict potential, and building social solidarity among students. This research contributes to the development of a pesantren-based tolerance education model that can be replicated in other Islamic educational institutions.